Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3sc50263e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocurrent generation by folding-driven H-aggregate formation

Abstract: A novel bis(merocyanine) dye has been synthesized and its folding and aggregation behavior has been elucidated in dependence on the solvent polarity. Extended cofacially p-stacked H-aggregates could be prepared in nonpolar solvents based on the preorganized folded dimer structure of the dye exhibiting a more than 120 nm hypsochromic shift of the absorption band. Furthermore, incorporation of such H-aggregate domains in bulk heterojunction (BHJ) solar cells by careful adjustment of processing conditions afforde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The solvent‐dependent spectral changes of 1 f (C5 spacer), 1 g (3‐oxopentyl spacer) and 1 h (C6 spacer) resemble those of C12‐tethered dye 1 k (see Figure S2c,d,e and Figure 2 c). The solvent‐dependent spectral changes of bis(merocyanine) dyes 1 e – k are accompanied by a clear quasi‐isosbestic point, respectively, as observed previously for dye 1 d with m ‐xylylene spacer,15 revealing a chemical equilibrium between two species, that is, the folded and the unfolded conformers of these molecules…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The solvent‐dependent spectral changes of 1 f (C5 spacer), 1 g (3‐oxopentyl spacer) and 1 h (C6 spacer) resemble those of C12‐tethered dye 1 k (see Figure S2c,d,e and Figure 2 c). The solvent‐dependent spectral changes of bis(merocyanine) dyes 1 e – k are accompanied by a clear quasi‐isosbestic point, respectively, as observed previously for dye 1 d with m ‐xylylene spacer,15 revealing a chemical equilibrium between two species, that is, the folded and the unfolded conformers of these molecules…”
Section: Resultssupporting
confidence: 75%
“…We have previously shown that, due to the accessibility of broad solvent permittivity range, tetrahydrofuran (THF; ε r =7.58)/methylcyclohexane (MCH; ε r =2.02) solvent mixtures are highly suitable to study merocyanine dye aggregation 15. 22 In nonpolar MCH aggregation of dipolar merocyanines is favored, while the interaction of dipole moments of dyes with polar THF stabilizes the monomeric species with respect to the aggregate 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclusively achieve the desired intramolecular aggregate by folding, THF had to be used for dimer F2 , as self‐assembly into larger aggregate structures was observed in MCH (Figure S2 in the Supporting Information); a similar case to this has also been observed for a bis(merocyanine) dye 8. 12 The monomeric reference compound F1 was almost insoluble in MCH, so it had to be dissolved in THF as well for comparison with the larger oligomer analogues. The absorption of F1 exhibited the characteristic features of a PBI monomer consisting of well‐resolved S 0 –S 1 vibronic structures at 425–550 nm without appreciable solvent dependence,13 whereas clear differences were observed in the absorption spectra of F2 and F8 depending on the number of building blocks and the solvent.…”
Section: Resultsmentioning
confidence: 81%
“…and characterization data of all MC dyes were123 reported previously[12,[24][25][26][27]. PC 61 BM (P99.5%) was obtained124 from Nano-C.…”
mentioning
confidence: 99%